Dissecting response to neoadjuvant immunotherapy-treated melanoma using cancer-immunity cycle-associated signatures - S. C. M. A. Wijnen; P. Dimitriadis; I. L. M. Reijers; A. M. Menzies; G. V. Long; L. F. A. Wessels; C. U. Blank (Cancer Immunology, Immunotherapy)
Abstract Neoadjuvant combination therapy with anti-PD-1 and anti-CTLA4 agents has significantly improved long-term survival in patients with metastatic melanoma, yet not all patients respond to treatment. Responders often exhibit upregulated baseline inflammatory signatures; however, these markers capture only a single facet of the Cancer-Immunity Cycle—a comprehensive model describing the sequential steps required for effective anti-cancer immunity. To determine whether non-responsiveness to immunotherapy arises from single or multiple ‘defective’ steps, we analyzed in melanoma patients, treated with neoadjuvant immunotherapy, gene signatures representing each step of the cycle. Patients not achieving a major pathological response showed overall lower expression of these signatures. Among the ‘immune-hot’ patients, we identified a low response subgroup defective in one step (‘homing-to-the-tumor,’ involving CXCL9 and CXCL10), making this a promising target for improving their outcomes.